Smart design : disruption, crisis, and the reshaping of urban spaces - Hu, Richard (New York, NY : Routledge, 2022)
"This book tackles the emerging smart urbanism to advance a new way of urban thinking and to explore a new design approach. It unravels several urban transformations in dualities: economic relationality and centrality, technological flattening and polarisation, and spatial division and fusion. These dualities are interdependent; concurrent, coexisting, and contradictory, they are jointly disrupting and reshaping many aspects of contemporary cities and spaces. The book draws on a suite of international studies, experiences, and observations, including case studies in Beijing, Singapore, and Boston, to reveal how these processes are impacting urban design, development, and policy approaches. The COVID-19 pandemic has accelerated many changes already in motion, and provides an extreme circumstance for reflecting on and imagining urban spaces. These analyses, thoughts, and visions inform an urban imaginary of smart design that incorporates change, flexibility, collaboration, and experimentation, which together forge a paradigm of urban thinking. This paradigm builds upon the modernist and postmodernist urban design traditions and extends them in new directions, responding to and anticipating a changing urban environment. The book proposes a smart design manifesto to stimulate thought, trigger debate, and, hopefully, influence a new generation of urban thinkers and smart designers. It will be of interest to scholars, students, and practitioners in the fields of urban design, planning, architecture, urban development, and urban studies"--
OCLC-licensed vendor bibliographic record.
Keywords: City planning -- Technological innovations; Urban policy; Smart cities; COVID-19 (Disease) -- Social aspects; ARCHITECTURE / Urban & Land Use Planning; HOUSE & HOME / Design & Construction